2019
DOI: 10.1109/access.2019.2927387
|View full text |Cite
|
Sign up to set email alerts
|

Locating Smartphones Indoors Using Built-In Sensors and Wi-Fi Ranging With an Enhanced Particle Filter

Abstract: Sensors-based and radio frequency (RF)-based indoor localization technology is one of the keys in location-based services. The IEEE 802.11-2016 introduced the Wi-Fi fine timing measurement (FTM) protocol, which provides a new approach for Wi-Fi-based indoor localization. However, Wi-Fi signals are susceptible to complex indoor environments. To improve the positioning accuracy and stability, an enhanced particle filter (PF) with two different state update strategies, a new criterion for divergence monitoring an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 36 publications
0
51
0
Order By: Relevance
“…Particles with low weight are then discarded, while new particles are sampled to keep the overall number of particles at a desired value. Particle filers have been applied to this problem as well [35].…”
Section: Particle Filtermentioning
confidence: 99%
“…Particles with low weight are then discarded, while new particles are sampled to keep the overall number of particles at a desired value. Particle filers have been applied to this problem as well [35].…”
Section: Particle Filtermentioning
confidence: 99%
“…The unscented Kalman filter (UKF) was finally utilized to fuse the robust dead reckoning and Wi-Fi FTM. Their experimental results showed that the mean positioning errors were within 2 m. Xu et al [38] provided two different strategies to update the particle set in the enhanced particle filter and employed it to combine the PDR and Wi-Fi FTM. The experimental results indicated that the mean positioning accuracy was approximately 1 m, and the new position was given within 0.5 second.…”
Section: Related Workmentioning
confidence: 99%
“…A mobile application relying on built-in smartphone sensors that emulates a pedestrian dead reckoning system with adaptive tilt compensation to estimate accurate headings in various linear displacements has been detailed by Xu et al [11].…”
Section: Current Contextmentioning
confidence: 99%